Pengaruh Good Corporate Governance (Gcg) Dan Corporate Social Responsibility (Csr) Terhadap Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Variable Intervening Pada Perusahaan Pertambangan Yang Go Public Di Bei - Ratih, Suklimah; Setyarini, Yulia (AKRUAL: JURNAL AKUNTANSI, 2014)
AbstractApplication of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) being demands for companles that have involved external parties in fullfilment of the operational funding and have social impact. The effective GCG and CSR will be able to increase the finance performance and value of the firms.This study aimed to determine the direct and indirect effect of GCG dan CSR against the value of the mining companies that go public in BEI, based on sample annual reports 2012. The result of this study is only the KPI (one element of GCG mechanism) that have dirrect effect to fFnancial Performance (ROA), and none of indirect effect hypothesis of GCG and CSR to Value of the Firm (Tobinâs Q) are proven.